2018
DOI: 10.1021/acs.jmedchem.8b00654
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of N-Phenyl-3-sulfamoyl-benzamide Derivatives as Capsid Assembly Modulators Inhibiting Hepatitis B Virus (HBV)

Abstract: Small molecule induced hepatitis B virus (HBV) capsid assembly modulation is considered an attractive approach for new antiviral therapies against HBV. Here we describe efforts toward the discovery of a HBV capsid assembly modulator in a hit-to-lead optimization, resulting in JNJ-632, a tool compound used to further profile the mode of action. Administration of JNJ-632 (54) in HBV genotype D infected chimeric mice resulted in a 2.77 log reduction of the HBV DNA viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…GLP-26 in combination with ETV potently decreased HBsAg and HBeAg levels in a humanized mouse model of infection, both during and, more importantly, after treatment. Previous studies have shown decreased HBV viral antigens during combination treatments (31), yet continued antiviral effects on these markers after treatment have not been yet reported for other CAMs from the same class, such as AB-423 (15) and JNJ-632 (32). The mechanisms resulting in the observed sustained response could arise from the very potent antiviral activity of GLP-26 (10 to 100 times more potent than AB-423 and JNJ-632) combined with a prolonged exposure from oral administration, leading to sustained efficacious levels of GLP-26.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-26 in combination with ETV potently decreased HBsAg and HBeAg levels in a humanized mouse model of infection, both during and, more importantly, after treatment. Previous studies have shown decreased HBV viral antigens during combination treatments (31), yet continued antiviral effects on these markers after treatment have not been yet reported for other CAMs from the same class, such as AB-423 (15) and JNJ-632 (32). The mechanisms resulting in the observed sustained response could arise from the very potent antiviral activity of GLP-26 (10 to 100 times more potent than AB-423 and JNJ-632) combined with a prolonged exposure from oral administration, leading to sustained efficacious levels of GLP-26.…”
Section: Discussionmentioning
confidence: 99%
“…82 However, similar compounds such as the 4,4-disubstituted-1,4-dihydropyrimidines 53a and 53b , developed by Janssen R&D Ireland, show weak anti-HBV activities using stable transfected cell lines HepG2.2.15 and HepG2.117 (IC 50 > 25 μ M). 83 …”
Section: Other Antiviral Agentsmentioning
confidence: 99%
“…The disadvantages of nucleoside analogs prompted us and other researchers to invent and find new structural non-nucleoside analog compounds [ 11 , 12 , 13 , 14 , 15 , 16 ]. Many anti-HBV bioactive non-nucleoside analog compounds have been designed and developed on the basis of their interactions with receptor using molecular docking [ 17 , 18 , 19 , 20 , 21 ]. When HBV receptor binding domain PreS1 and PreS2 protein (including L protein, M protein and S protein) interact with small molecules, the virus will not allow entry to hepatocyte.…”
Section: Introductionmentioning
confidence: 99%